Virtual Education in Islamic Azad Universities of Sistan and Baluchestan Province: Identifying Components and Outcomes - Naseripour, Aghil; Shariatmadari, Mehdi; Kordestani, Fereshteh; Hamidifar, Fatemeh (Management Strategies and Engineering Sciences, 2025)
The objective of this study is to identify the components and outcomes of virtual education in Islamic Azad Universities of Sistan and Baluchestan Province. This research employs a mixed-methods approach (qualitative-quantitative) with an exploratory sequential design. In the qualitative phase, the grounded theory method was applied, while the quantitative phase utilized a survey method. In the qualitative phase, the research sample consisted of 20 experts in the field of educational management, selected using criterion-based purposive and snowball sampling methods. Semi-structured interviews were conducted with these individuals. In the quantitative phase, the statistical population comprised students of Islamic Azad Universities in Sistan and Baluchestan Province (28,811 individuals), from which a sample of 379 students was selected using random sampling. The research instrument in the quantitative phase was a researcher-developed questionnaire, designed based on the theoretical model derived from expert opinions in the qualitative phase. For qualitative data analysis, MAXQDA software and Straussian grounded theory were employed, while quantitative data were analyzed using structural equation modeling. The components of virtual education included types of virtual education, characteristics of teaching methods, and assessment of education, with the characteristics of virtual teaching methods having the most significant impact. The outcomes of virtual education encompassed both positive and negative consequences, with positive outcomes carrying the highest factor loading. Overall, the findings of the quantitative phase confirmed the results of the qualitative phase. The results of this study emphasize the necessity of strengthening the characteristics of virtual teaching methods to enable individuals to use this space effectively and consciously. Moreover, positive outcomes play a more central role in the present analysis, which can be instrumental in designing policies and strategies to mitigate negative outcomes.